The Price of Prejudice - Hedegaard, Morten Størling; Tyran, Jean-Robert (American economic journal. Applied economics, 2018)
We present a new type of field experiment to investigate ethnic prejudice in the workplace. Our design allows us to study how potential discriminators respond to changes in the cost of discrimination. We find that ethnic discrimination is common but highly responsive to the “price of prejudice,” i.e., to the opportunity cost of choosing a less productive worker on ethnic grounds. Discriminators are on average willing to forego 8 percent of their earnings to avoid a coworker of the other ethnic type. The evidence suggests that animus rather than statistical discrimination explains observed behavior.